A rare male patient with classic Rett syndrome caused by MeCP2_e1 mutation. Issue 3 (17th January 2018) - Tokaji, Narumi; Ito, Hiromichi; Kohmoto, Tomohiro; Naruto, Takuya; Takahashi, Rizu; Goji, Aya; Mori, Tatsuo; Toda, Yoshihiro; Saito, Masako; Tange, Shoichiro; Masuda, Kiyoshi; Kagami, Shoji; et al.
Abstract : Rett syndrome (RTT) is a severe neurodevelopmental disorder typically affecting females. It is mainly caused by loss‐of‐function mutations that affect the coding sequence of exon 3 or 4 of methyl‐CpG‐binding protein 2 ( MECP2 ). Severe neonatal encephalopathy resulting in death before the age of 2 years is the most common phenotype observed in males affected by a pathogenic MECP2 variant. Mutations in MECP2 exon 1 affecting the MeCP2_e1 isoform are relatively rare causes of RTT in females, and only one case of a male patient with MECP2‐related severe neonatal encephalopathy caused by a mutation in MECP2 exon 1 has been reported. This is the first reported case of a male with classic RTT caused by a 5‐bp duplication in the open‐reading frame of MECP2 exon 1 (NM_001110792.1:c.23_27dup) that introduced a premature stop codon [p.(Ser10Argfs*36)] in the MeCP2_e1 isoform, which has been reported in one female patient with classic RTT. Therefore, both males and females displaying at least some type of MeCP2_e1 mutation may exhibit the classic RTT phenotype.